Systematic Review Analysis on Health Services During the COVID-19 Pandemic in a Political Perspective - Elyta Elyta; Herlan Herlan (UIN Sunan Gunung Djati, 2024)
The aim of the Systematic Review in this research is to analyze the health service model during the COVID-19 pandemic. Health services are an important part of handling the COVID-19 pandemic. This research is important for examining the formulation of health service policies during the COVID-19 pandemic by identifying themes related to research variables related to health service policies. The benefits of this research can be used as reference material in formulating optimal health service policies during the COVID-19 pandemic. This research uses a literature study of 362 Scopus Indexed International Journals, analyzed using Vosviewer and Nvivo 12 plus software. The results of this research show; 1) Studies related to health services on the number of COVID-19 cases experienced a significant increase during the 2020-2021 period, this shows the ability of the health service system to develop; 2) Health services in each region and country vary depending on the situation and capabilities of each region; 3) the results of the network analysis visualization analysis formulate an effective health service model.